Pembuatan Kurikulum Pelatihan untuk Program Management trainee di PT X - Belinda Kristanto; Prayonne Adi (Jurnal Titra, 2017)
This research was conducted to create training curriculum that can be used as supporting tool for Management trainee Program of PT X. The research is focused on two key research area of general competency and one key research area of particular competency. Curriculum is formed of five main components, which is objective, topic, method, media, evaluation. The objective was divided into general instructional objective dan particular instructional objective. There are fifty-eight topics that has been appointed and merged into thirteen training session. The methods are class room training, on the job training, job rotation, dan project assignment.The medias are demonstration, three dimensional (3D) object, visual media, projected still media, and projected motion media. The type of evaluation that will be done is written test, practice, presentation, and project assignment’s scoring.